2009
DOI: 10.3909/ricm0480
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity in Patients With Congestive Heart Failure

Abstract: Obesity is a known risk factor for developing cardiovascular disease, including heart failure. However, the impact of obesity on patients with heart failure is unclear. Weight reduction is a recommended method of prevention of cardiovascular disease. However, the phenomenon of the "obesity paradox" (or "reverse epidemiology") revealed that overweight and mild to moderate obesity are associated with better outcomes in patients with heart failure compared with patients at normal or ideal weight. Even more, incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 208 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, our study found significantly decreased risks of CHF, cardiac arrest, pneumonia, arrhythmia, and transfusion in obese patients compared to non-obese patients. This decrease in CHF, cardiac arrest, and arrhythmia could be explained by what is known as the “obesity paradox,” where BMI and mortality are inversely related [ 17 , 18 ]. This paradox theorizes that obesity may be protective and linked to higher survival rates in elderly and chronically ill populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, our study found significantly decreased risks of CHF, cardiac arrest, pneumonia, arrhythmia, and transfusion in obese patients compared to non-obese patients. This decrease in CHF, cardiac arrest, and arrhythmia could be explained by what is known as the “obesity paradox,” where BMI and mortality are inversely related [ 17 , 18 ]. This paradox theorizes that obesity may be protective and linked to higher survival rates in elderly and chronically ill populations.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps this is due to higher rates of CHF, pneumonia, and transfusion in non-obese patients during the first 90 days. Previous studies have found reduced mortality from CHF and pneumonia and decreased need for transfusion [ 17 , 24 , 25 ]. This decrease in mortality could reduce the amount of healthcare intervention required and, therefore, reduce the associated healthcare costs.…”
Section: Discussionmentioning
confidence: 99%
“…While this seems contradictory, other studies have found this same phenomenon called the "obesity paradox", where BMI and mortality are inversely related, and this could explain the decrease in odds of cardiac arrest and arrhythmia. 28,29 Even this paradox is controversial, however, because it could be due to retrospective data with obese patients being diagnosed earlier or due to a lack of proper adjustments for cardiorespiratory fitness as a high BMI due to fat and due to muscle are different. 30 Furthermore, patients in the non-obese group could have been obese previously, but then experienced illness related weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies have described a paradoxical relation between a high BMI and the prognosis of patients with coronary artery disease and HF, called the obesity paradox ( 3 , 5 , 8 13 ). According to this theory, contrary to expectations, overweight or patients with obesity have a better prognosis in heart diseases when related to low or normal weight patients ( 3 , 8 , 9 , 12 , 14 ).…”
Section: Introductionmentioning
confidence: 78%